¿Vencer los estereotipos? El discurso sobre las violencias de género en tres melodramas de Televisa: “Vencer el miedo”, “Vencer el desamor” y “Vencer el pasado” - Gómez Rodríguez, Gabriela (2023)
In 2019 Televisa began the production and transmission of three telenovelas with the central theme of gender violence. The trilogy, Vencer el miedo, Vencer el Desamor y Vender el Pasado, intertwines the stories of four protagonists who experience different conflicts associated with the multiple forms of violence they face in their daily relationships with men and women. This article analyzes these telenovelas from the gender perspective and the Critical Discourse Analysis (CDA) method. Among our findings, it stands out that, although there are advances in the way of representing women, the symbolic constructions and discursiveness around the female characters continue to yield to the norms of Christian morality, physical stereotypes or the more traditional roles assigned to men and women.